Pengaruh metode sosiodrama terhadap hasil belajar dan sikap tanggung jawab dalam pembelajaran PKn - Premita Sari Octa Elviana; Mukhamad Murdiono (Jurnal Civics: Media Kajian Kewarganegaraan)
This study aimed to analyze: (1) the significant effect of the socio-drama method with texts are written by teacher on the students’ learning outcome; (2) with texts are written by students on the students’ learning outcome; (3) with texts are written by teacher on the students’ responsibility attitudes; (4) with texts are written by students on the students’ responsibility attitudes; (5) the effectiveness of socio-drama method with texts are written by students and socio-drama method with texts are written by teacher for learning outcomes and attitude of responsibility. This type is a quasi- experiment with pretest-posttest control group design. The population was the 10th Grade Students SMA Negeri 8 Kota Kediri 2016/2017 school year. The study findings are as follows: (1) the socio-drama method with texts are written by teacher does not have significant influence on the students’ learning outcome; (2) the socio-drama method with texts are written by students has significant influence on the students’ learning outcome; (3) the socio-drama method with texts are written by teacher does not have significant influence on the students’ responsibility attitudes; (4) The socio-drama method with texts written by students has significant influence on the students’ responsibility attitudes; (5) Socio-drama method with texts are written by students more effective than socio-drama method with texts are written by teacher on the students’ learning outcome and responsibility attitudes.